The optimization method for synthesis of technetium-99m-luteolin as radiotracer in the development of cancer drugs from flavonoid - Danni Ramdhani; Maula Eka Sriyani; S Fairuz Nabila (Wolters Kluwer Medknow Publications, 2020)
The aim of this study is to find the optimum conditions of labeling luteolin flavonoid compounds with technetium-99m (99mTc) to meet the purity requirements stated in the United States Pharmacopeia. This compound is expected to be a potential radiotracer compound for diagnosing cancer. The optimization method in labeling luteolin with technetium determines the parameters such as pH, SnCl2.2H2O, genistein concentration, and incubation time. Optimization results of Technetium-99m-luteolin labeling obtained optimum pH conditions 8, the amount of SnCl2.2H2O as a reducing agent 60 μL, the optimum amount of luteolin 6 mg/ml, and the optimum incubation time is 30 min. This optimum condition obtained a99mTc-Luteolin radiochemical purity yield of 94.15%. The radiochemical purity percentage of the99mTc-Luteolin compound has fulfilled the requirements listed at United States Pharmacopeia, which is ≥90%.